Michigan High School Science Teacher Perceptions Of Futures Magazine As A Pedagogical Resource And Career Exploration Tool - Murari Suvedi; Kirk Heinze; Maxine Ferris (Journal of Applied Communications, 1991)
The primary objective of the study was to determine whether Futures, the quarterly magazine of the Michigan Agricultural Experiment Station (MAES), has helped high school science teachers gain a greater awareness and understanding of agricultural and natural resources research.